Kesantunan Berbahasa dalam Perspektif Islam di Era 5.0 - R. Tamtam Kamaluddin; Nandang Rukanda (CV. Creative Tugu Pena, 2026)
This study aims to analyze language politeness based on Islamic values in the Society 5.0 Era and its relevance in addressing the challenges of modern digital communication. The development of information technology and social media in the Society 5.0 Era has brought significant changes to people's communication patterns. On the one hand, these developments provide convenience in information exchange; however, on the other hand, they also create various communication ethics issues, such as hate speech, cyberbullying, hoaxes, and the use of impolite language in digital spaces. This study employed a qualitative approach using library research methods. Data were obtained from the Qur’an, Hadith, books, scientific journals, and previous studies related to language politeness, Islamic communication, and digital literacy. The data analysis technique used content analysis through the stages of data reduction, categorization, interpretation, and conclusion drawing. The results indicate that Islamic communication principles such as qaulan sadidan (truthful speech), qaulan ma‘rufan (kind speech), qaulan layyinan (gentle speech), and qaulan kariman (honorable speech) are highly relevant in developing polite, ethical, and humane digital communication. This study also found that the decline in language politeness in digital media is influenced by instant communication culture, social media anonymity, and weak ethics-based digital literacy. Therefore, strengthening character education, Islamic values-based digital literacy, and the use of social media as a medium for education and da’wah are important strategies for building a civilized communication culture in the Society 5.0 Era. This study contributes conceptually to the development of linguistics, Islamic communication, and modern digital communication ethics studies.